Pengelolaan Pembelajaran IPA Menggunakan Model Snowball Throwing dan Cooperative Integrated Reading And Composition (CIRC) untuk Meningkatkan Motivasi Belajar dan Kemampuan Reading Comprehension Siswa KelaS VIII SMP PGRI Kambu - Mahrun M.Pd.; Ardiansyah; Mujiono Sang Putra; Sri Wulandari (JPSL : Jurnal Pendidikan, Sosial dan Lingkungan, 2023)
Experimental research by designtreatment by level 1 (1 treatment and one attribute variable learning motivation and abilityReading Comprehension class eight students of Junior high school PGRI Kambu In this design, learning consists of learningmodel Snowball Throwing  and learningmodel Cooperative Integrated Reading dan Composition (CIRC) is a treatment variable. While student motivation consists of high learning motivation and low learning motivation is an attribute variable. As the dependent variable in this study is abilityReading Comprehension Student. As for the results of research on the management of science learning by using a modelsnowball throwing and CIRC to increase students' learning motivation and abilityReading comprehension it can be concluded that science learning uses a modelsnowball throwing andCIRC regularlyblanded can increase learning motivation and abilityReading comprehension student. In the experimental class, the average value was 77.6% and increased to 81.6%, and the test resultsreading comprehension in the experiment 78.8%, while in the control class 68.9%.